2023
DOI: 10.1371/journal.pone.0278836
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the external exposome and its contribution to the clinical respiratory and early biological effects in children: The PROMESA cohort study protocol

Abstract: Background Air pollution contains a mixture of different pollutants from multiple sources. However, the interaction of these pollutants with other environmental exposures, as well as their harmful effects on children under five in tropical countries, is not well known. Objective This study aims to characterize the external exposome (ambient and indoor exposures) and its contribution to clinical respiratory and early biological effects in children. Materials and methods A cohort study will be conducted on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The concept of the “exposome” aims to comprehensively analyze an individual’s lifetime exposure to environmental factors. By exploring the exposome, researchers aim to unravel the complex relationship between environmental exposures and health, potentially providing new insights into disease causation and prevention, and personalized therapeutic strategies [ 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the “exposome” aims to comprehensively analyze an individual’s lifetime exposure to environmental factors. By exploring the exposome, researchers aim to unravel the complex relationship between environmental exposures and health, potentially providing new insights into disease causation and prevention, and personalized therapeutic strategies [ 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that lower values of FEV 1 were associated with prenatal perfluorononanoate and perfluorooctanoate exposures, as well as with 9 postnatal exposures (copper, ethyl-paraben, phthalate metabolites concentrations, house crowding, and facility density around schools), whereas the inverse distance to the nearest road during pregnancy was associated with a higher FEV 1 (22). More recently, the PROMESA cohort study protocol aims to characterize the external exposome (ambient and indoor exposures) and its contribution to clinical respiratory and early biological effects in children under five in tropical countries (23).…”
Section: The Exposome: An Innovative Approach For Assessing Environme...mentioning
confidence: 99%
“…In a subgroup of patient's genetic markers help to predict severity 28 or comorbidity. 29 Knowing that lifestyle factors and the exposome [30][31][32][33][34] are key factors regarding epigenetics and activating and silencing of genes, the environment is a target for prevention. [30][31][32][33][34] However, given the complexity, apart from general recommendations like avoidance of tobacco smoke exposure, 35 control of pollution and the beneficial environment of a farming community and/or dog keeping, 24,30 no clear preventive strategies are available for the prevention of allergic airway disease and asthma in childhood.…”
Section: De Aling With T Ype 2 Infl Ammati On In the Ped Iatri C P Op...mentioning
confidence: 99%